Analisis Kelayakan Investasi Proyek Pembangunan Asvara Resort Manuaba Ubud - Dewi, I Gusti Ayu Wulan Krisna; Pramana, I Made Wahyu; Sudiarta, I Komang (Jurnal Talenta Sipil, 2024)
The current property competition in Bali, marked by an increase in the construction of hotels, villas, and resorts, coupled with the fluctuating growth rate of tourist visits over the past five years due to the pandemic (with both increases and decreases), necessitates a reevaluation of the investment feasibility analysis for the construction of Asvara Resort Manuaba Ubud. This study aims to assess the market, technical, and financial feasibility aspects of the investment in the construction of Asvara Resort Manuaba Ubud, to determine whether this development remains profitable for investors. Additionally, it seeks to ensure that the benefits of this resort development can be felt by the government and the surrounding community, thus supporting the welfare and economy of the region, especially Gianyar Regency. To analyze the market aspect, data on the number of tourists visiting Bali, occupancy rates, and the availability of similar resorts in the surrounding area, obtained from government agencies and several star-rated hotels in the vicinity, are required and then processed using forecasting methods. For the technical aspect analysis, geographical location data, project location, and land utilization plans are analyzed using qualitative descriptive methods. For the financial aspect analysis, data on costs and revenues obtained from contractors and operators are analyzed using Net Present Value (NPV), Benefit Cost Ratio (BCR), Payback Period (PP), and Internal Rate of Return (IRR) parameters. The market aspect analysis results show an increase in tourist visits, including occupancy rates, which will positively impact visits to this resort. From the technical aspect, land utilization and allocation have been optimized for investment. Financially, the NPV value is Rp 16,706,385,995.27, the IRR is 19.67%, the BCR is 1.242, and the PP is 10 years. The sensitivity analysis results, considering the worst-case scenario where all revenue components decrease by 8% and costs increase by 8%, show an NPV value of Rp 1,215,020,196.08, an IRR of 17.13%, a BCR of 1.018, and a PP of 13 years. Overall, it can be concluded that this investment is feasible for investors.